Negosiasi Nilai Akhlak Islam di Ruang Digital: Studi Kualitatif tentang Pembelajaran Pendidikan Agama Islam di SMA N 1 Blora pada Era Algoritma Media Sosial - Siti Nur’aini; Puspitarani; Kristyuana; Sultan Mahi Salama; Achmad Irchamni; M. Kasheem (Attractive : Innovative Education Journal, 2026)
The development of algorithm-based social media has had a major impact on students' interpretation of Islamic moral values, leading to a new turning point in Islamic Religious Education (IRE) at SMAN 1 Blora. IRE is not only carried out in a space representative of digital influence, but also interacts dynamically with students' religious experiences in the digital space. The purpose of this study is to examine how Islamic moral values are negotiated in IRE learning at SMAN 1 Blora in the era of social media algorithms. This study uses qualitative methodology and case study design. Data were collected through in-depth interviews, observation of the learning process, and analysis of learning documents. The research subjects were IRE teachers and high school students. Data analysis was conducted using thematic analysis techniques, which included data reduction, data presentation, and conclusion drawing. The results showed that PAI teachers helped students understand the material, encouraged them to think critically, and linked their digital experiences to Islamic moral values. These values are obtained through students' interaction with social media content. Conversely, students tend to interpret moral values based on their digital experiences and social environment. The results show that Islamic moral values in the digital age are internalized through a dialogical negotiation process, rather than one-way transmission. This study provides empirical contributions to the development of Islamic Education learning that adapts to the dynamics of social media in high schools.